The spatial (in)stability of mental health calls for police service - Koziarski, Jacek (Criminology & public policy, 2023)
Research summary Inspired by studies on crime concentration, scholars have begun examining the spatial patterns of other issues under the police mandate, such as calls for service involving persons with perceived mental illness (PwPMI). While findings show that PwPMI calls for service concentrate in a few number of places, we do not know whether the concentration of these calls fall within a narrow bandwidth of spatial units nor whether these calls are spatially stable. Drawing on 7 years of calls for service data from the Barrie Police Service, this study tests for the temporal stability of PwPMI call for service concentrations at two units of spatial analysis and applies a longitudinal variation of the Spatial Point Pattern Test to assess the spatial stability of these calls at both the global and local levels. The results reveal that concentrations of PwPMI calls for service not only fall within a narrow proportional bandwidth of spatial units, but are spatially stable, even during the COVID-19 pandemic. Policy implications Existing police- and community-based efforts that respond to PwPMI in the community are tasked with responding to crises that could have been prevented with timelier intervention. Drawing from crime-focused, place-based policing strategies whose deployment is informed by the spatial concentration of crime, scholars have similarly argued that knowledge on where PwPMI calls for service concentrate can be leveraged to inform and deploy place-based efforts whose focus is to assist PwPMI in a proactive capacity. The findings of the present study further substantiates the deployment of PwPMI-focused police- and community-based resources as proactive, place-based efforts. In doing so, these efforts could not only prevent mental health crises from occurring but could prevent future police-involved calls for service and thus reduce the footprint of the police in the lives of PwPMI in a reactive capacity.